Variability of meteorological droughts in the polish and the Ukrainian Carpathians, 1984–2015 - Kholiavchuk, Dariia; Cebulska, Marta (Meteorology and Atmospheric Physics, 2022)
The article addresses the occurrence and severity of meteorological droughts in terms of the deficit of monthly precipitation and the Standardized Precipitation Index (SPI) in the Polish and the Ukrainian Carpathians in the period from 1984 to 2015.The biggest number of cases with the lowest monthly precipitation in a year are found in April both in the Polish and theUkrainian Carpathians both—9% and 6%, respectively. Insufficient monthly precipitation sums were most frequently characteristic of June and September, with the frequency slightly above 16%. In the other months, the frequency of dry periods in different ranges of SPI exceeded 12%. The months with meteorological drought observed in the whole or a major part of the study area at the same time are accounted for by the prevalence of anticyclonic situations, especially the western sector anticyclone and the anticyclonic wedge. Meteorological droughts covering a major part of the area are the most intense and lasting in the first (1986–1987) and last (2013–2015) decades of the entire period, except for the highest Ukrainian station ofPogegevskaya. The longest meteorological droughts with SPI-12 ≤ − 2.0 are characteristic of the transboundary region between the Eastern and the Western Carpathians, the Eastern Beskids in the first decade and the last decade of the 1984–2015 period. The north-western and northern foothills of the Polish Carpathians, the leeward south-eastern macroslope of the Ukrainian Carpathians, and closed intermountain valleys are most prone to meteorological droughts.